Potential protective regulatory effects on radiation−induced esophageal injury in TUT4−/− mice - Ren, Huiwen; Li, Wei; Fan, Zhigang; Wang, Jianlin; Sun, Zhiqiang; Huang, Renhua; Luo, Judong; Gao, Bo (Frontiers in Oncology, 2025)
IntroductionTerminal uridyl transferase 4 (TUT4), a nucleotide transferase that modifies miRNA sequences, plays a critical role in regulating miRNA target interactions and function. However, its involvement in radiation-induced esophageal injury remains poorly understood.MethodsTo investigate this, we performed computational analysis of RNA-seq data from irradiated esophageal tissues of wild-type and TUT4-knockout (TUT4–/–) mice, identifying 53 differentially expressed mRNAs (DEmRNAs), of which 30 were upregulated and 23 downregulated.ResultsGene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses revealed that these DEmRNAs were significantly associated with biological processes including lipid metabolism, fatty acid metabolism, proteolysis, and broader metabolic functions. Notably, DEmRNAs in TUT4–/– esophageal tissues showed marked enrichment in the renin–angiotensin system and peroxisome proliferator-activated receptor signaling pathways, implicating their potential roles in the pathogenesis of radiation-induced esophageal injury. In addition, we identified a regulatory axis in which a long non-coding RNA competes with miR-182 to modulate the competing endogenous RNA network governing TUT4 target genes. Collectively, our transcriptomic analysis offers novel mechanistic insights into how TUT4 may confer protection against radiation-induced damage in esophageal tissues.